Games of History Games and Gaming as Historical Sources - Spanos, Apostolos (Routledge Guides to Using Historical Sources, 2021)
Games of History provides an understanding of how games as artefacts, textual and visual sources on games and gaming as a pastime or a "serious" activity can be used as sources for the study of history. From the vast world of games, the book's focus is on board and card games, with reference to physical games, sports and digital games as well. Considering culture, society, politics and metaphysics, the author uses examples from various places around the world and from ancient times to the present to demonstrate how games and gaming can offer the historian an alternative, often very valuable and sometimes unique path to the past. The book offers a thorough discussion of conceptual and material approaches to games as sources, while also providing the reader with a theoretical starting point for further study within specific thematic chapters. The book concludes with three case studies of different types of games and how they can be considered as historical sources: the gladiatorial games, chess and the digital game Civilization. Offering an alternative approach to the study of history through its focus on games and gaming as historical sources, this is the ideal volume for students considering different types of sources and how they can be used for historical study, as well as students who study games as primary or secondary sources in their history projects.